Impact of Public Debt on Economic Growth: A Panel ARDL Approach in ASEAN-5 - Jane Rose Bacay; Justine Diokno; Kimberly Anne Iguiz; Ronaldo Cabauatan (UJoST- Universal Journal of Science and Technology, 2022)
This study examined the relationship between public debt and economic growth by employing the autoregressive distributed lag (ARDL) approach developed by Pesaran and Shin (1999) in the ASEAN-5 from 1986 to 2020. This paper considered a time period wherein there exists an episode of economic uncertainties. The other variables used in this study are exchange rate, foreign exchange reserves, and world uncertainty index. The data were extracted from the World Development Indicators (WDI) of the World Bank and the International Monetary Fund (IMF). It is essential to determine whether or not debt financing is a sound fiscal policy, particularly during an economic crisis, to protect a country’s fiscal condition. The empirical analysis indicated a significant negative relationship between public debt and economic growth in the long run but an insignificant relationship in the short run. Specifically, an increase in public debt by 1% is associated with a 3.74% decrease in economic growth in the long run. This finding supports several previous studies, and it implies that governments need effective public debt management to mitigate the long-term impact of public debt. The results also suggest that public debt should be allocated to productive sectors and long-term investment projects to ensure debt sustainability.